Exploring Bandung Public Bus Commuter Satisfaction and Loyalty - Faridian Wirayat, Mohamed Yusuf; Belgiawan, Prawira Fajarindra (Unit Research and Knowledge, School of Business and Management, Institut Teknologi Bandung, 2023)
Bandung, the capital of West Java, is 2021 Indonesia's most crowded city. Congestion happens even then since the number of cars in Bandung has grown by an average of 11% annually. To overcome the congestion, the Ministry of Transportation Republic Indonesia programme created the